In Suspension: Memory of Indonesian Migrant Women Returnees in Cities - Kilim Park (Parahyangan Center for International Studies, 2015)
This paper attempts to propose new ways to understand Indonesian migrant women workers and their lives, particularly at the intersection of memory and urban life. I explore the role of memory in the urban life of Indonesian migrant women returnees by examining the ways in which their memory affects seemingly mundane yet central details of their new life and opens up a space to expose and disrupt the workings of state and society that pushes women into the margin. Focusing on a growing number of migrant women who are settling themselves in urban areas upon completing their work overseas, I consider how their memory, suspended in the present, contributes to normalizing the anomaly by confronting and refusing public articulations of power vis-a-vis the feminine and the rural in Indonesia.